2021
DOI: 10.2147/dddt.s314562
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Celecoxib, Dezocine and Dexmedetomidine in Beagle Plasma Using UPLC-MS/MS Method and the Application in Pharmacokinetics

Abstract: Background An efficient, fast and sensitive ultra high-performance liquid chromatography-mass spectrometry (UPLC-MS/MS) method for simultaneous determination of celecoxib (CEL), dezocine (DEZ) and dexmedetomidine (DEX) in beagle plasma were established. Methods The beagle dogs plasmawas precipitated by acetonitrile. The column was Acquity UPLC BEH C18 column and the mobile phase was acetonitrile-formic acid with gradient mode, and the flow rate was set at 0.4 mL/min. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Therefore, it is often used in the detection of biological samples, the study of pharmacokinetics and DDI. 15 , 20 , 21 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is often used in the detection of biological samples, the study of pharmacokinetics and DDI. 15 , 20 , 21 …”
Section: Resultsmentioning
confidence: 99%
“…Dex has a significant analgesic effect, which can reduce the use of morphine on the first day after surgery, relieve the pain of patients, and reduce the occurrence of postoperative nausea, vomiting, dizziness, and other adverse reactions. Dex combined with dezocine is very safe in monitoring anesthesia, and the analgesic effect is significantly increased when the two drugs are used in combination, but the sedative effect does not superimpose [24,25]. This study found that the onset time of sensory block, recovery time, and time spent in PACU in the experimental group were significantly shorter than those in the control group, the time of anesthesia maintenance was significantly greater than that in the control group, the use of intravenous analgesics was also significantly lower than that in the control group, and the incidence of adverse reactions (nausea, vomiting, dizziness) was also significantly smaller than that in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is often used in the detection of drug concentration in biological samples, the study of pharmacokinetics and DDI. 19,20 Fedratinib and upadacitinib were JAK inhibitors. Fedratinib was a selective JAK2 inhibitor for the treatment of adult patients with myelofibrosis (MF).…”
Section: Methods Validation and Improvementmentioning
confidence: 99%